PQRST Technique on Students’ Reading of Hortatory Exposition Text - Firdha Aulia; Fahriany Fahriany; Desi Nahartini (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aimed to find the empirical evidence of the Effect of Using PQRST Technique on Students’ Reading in Hortatory Exposition Text at the eleventh-Grade of SMAN 1 Sukaraja in Academic Year 2020/2021. The population of this study was the eleventh grade of SMAN 1 Sukaraja. The sample was 70 students selected by using purposive sampling technique and was divided into two classes; experimental class and controlled class. The method used in the study was a quantitative method using a quasi-experimental design. Research instrument of this study was pre-test and post-test. The data was then analyzed by using the T-Test. Using T-Test to compare the value of to and T-Table, to is higher than T-Table (to t-table). The result obtained from this study showed the effectiveness of using the PQRST technique on students’ Reading in Hortatory Exposition text. Based on the results of data analysis from the pre-test, the average of study result gained in tests with the average value was 69,5, and the average of study result gained in post-test was 82,2. Whereas, in post-test after the researcher applied PQRST technique was increased 12,7 points from the pre-test. This research proved that the PQRST technique affected students’ reading in hortatory exposition text on eleventh-grade at SMAN 01 Sukaraja.